The quest for the holey pail - Willson, Sarah (New York : Simon Spotlight/Nickelodeon, 2000)
Angelica and the Rugrats find themselves in Camelot, where they try to recover her doll and rescue Grandpa Lou.
Keywords: Camelot (Legendary place) -- Fiction; Knights and knighthood -- Fiction; Time travel -- Fiction